Pengaruh Rasio Capital Adequacy Ratio, Net Interest Margin, Non Performing Loan Terhadap Return On Asset Bank Konvensional Periode 2014 -2022 - Ketut Adhi Wiyana Wirawan (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2024)
This research was conducted to fill the gap in previous studies regarding the differing opinions on the impact of Capital Adequacy Ratio, Net Interest Margin, and Non-Performing Loan on Return on Assets (ROA). The focus was on the phenomenon of the gap in the relationship between ROA and bank financial performance. The aim was to evaluate the influence of Capital Adequacy Ratio, Net Interest Margin, and Non-Performing Loan on ROA both separately and together in these banks during the period of 2014-2022. The research method employed was a quantitative approach using purposive sampling technique to select samples consisting of five leading conventional banks in Indonesia. The analysis results using multiple linear regression and hypothesis testing revealed that the impact of Capital Adequacy Ratio on ROA was not significant, Net Interest Margin had a significant positive impact on ROA, Non-Performing Loan had a significant negative impact on ROA, and collectively, Capital Adequacy Ratio, Net Interest Margin, and Non-Performing Loan had an impact on ROA.